Gallbladder Cancer Progression Is Reversed by Nanomaterial-Induced Photothermal Therapy in Combination with Chemotherapy and Autophagy Inhibition - Cai Q (Dove Medical Press, 2020)
Qiang Cai, 1, 2,* Xinjing Wang, 2,* Shouhua Wang, 1 Longyang Jin, 1 Jun Ding, 3 Di Zhou, 1 Fei Ma 4 1Department of General Surgery, Xinhua Hospital, Shanghai JiaoTong University School of Medicine, Shanghai 200092, People’s Republic of China; 2Department of General Surgery, Shanghai Institute of Digestive Surgery, Ruijin Hospital, Shanghai JiaoTong University School of Medicine, Shanghai 200025, People’s Republic of China; 3Department of Biliary and Pancreatic Surgery, Shanghai Shuguang Hospital Affiliated with Shanghai University of T.C.M., Shanghai 201203, People’s Republic of China; 4Department of Oncology, Xinhua Hospital, Shanghai JiaoTong University School of Medicine, Shanghai Institute for Pediatric Research, Shanghai 200092, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei MaDepartment of Oncology, Xinhua Hospital, Shanghai JiaoTong University School of Medicine, Shanghai Institute for Pediatric Researh, 1665 Kongjiang Road, Shanghai 200092, People’s Republic of ChinaEmail Mafei@xinhuamed.com.cnDi ZhouDepartment of General Surgery, Xinhua Hospital, Shanghai JiaoTong University School of Medicine, 1665 Kongjiang Road, Shanghai 200092, People’s Republic of ChinaEmail Zhoudi@xinhuamed.com.cnIntroduction: Gallbladder cancer (GBC) is the most common malignancy in biliary tract with extremely poor prognosis. Photothermal therapy (PTT) shows great promises for tumor therapy, which causes tumor cell death via selectively directed heating released by nanoparticles under the near-infrared irradiation. Through degrading damaged organelles and misfolded proteins in autophagosomes, autophagy plays a vital role in maintaining the intracellular homeostasis. The present study attempted to combine chemotherapy and autophagy blocking with PTT.Materials and Methods: We purchased multi-walled carbon nanotubes from Nanostructured and Amorphous Materials and performed PTT using an 808-nm diode laser. The cytotoxic effects of PTT and chemotherapy in vitro were assessed by cell viability analysis. The effects of PTT and chemotherapy on autophagy in vitro were assessed by GFP-LC3 and Western blot. And these results were confirmed by in vivo experiment.Results: Both PTT and chemotherapy could trigger cytoprotective autophagy to tolerate the cellular stresses and prolong the survival of GBC cell; therefore, the blocking of autophagy could enhance the efficacy of PTT and chemotherapy in GBC treatment in vitro and in vivo.Conclusion: Chemotherapeutic drug doxorubicin and autophagy inhibitor chloroquine could enhance the efficacy of nanoparticle-mediated hyperthermia in GBC.Keywords: gallbladder cancer, photothermal therapy, carbon nanotubes, chemotherapy, autophagy